Long-term information, short-lived derivative securities - Dan Bernhardt; Ryan Davies; John Spicer (Queen's University, Department of Economics, 2000)
This paper explores strategic trade in short-lived derivative securities by agents that possess long-term information about an underlying asset. In contrast to trading equity, where an informed agent will ultimately benefit from his trades, trading short-lived securities is profitable only if the price impounds the private information before expiry. A consequence is that a risk neutral informed agent's holdings of the short-lived security affect his trading behavior: Past informed trading leads to greater future informed trading. The shorter horizon in which information must be impounded for a short-lived security to pay off makes an informed agent more reluctant to trade at earlier dates. By characterizing the conditions under which liquidity traders choose to incur extra costs to roll over their short-term positions rather than trade in longer-term derivative securities, we provide a possible explanation for why most markets for longer-term derivative securities have little liquidity and large bid-ask spreads.
Keywords: G1; D8; 330; Private information; liquidity; derivative securities; strategic trade